Telephone coaching for the prevention of depression in depression in farmers: Results from a pragmatic from a pragmatic randomized controlled trial - Thielecke, Janika; Buntrock, Claudia; Titzler, Ingrid; Braun, Lina; Freund, Johanna; Berking, Matthias; Baumeister, Harald; Ebert, David D. (Journal of Telemedicine and Telecare, 2022)
Introduction Farmers have a high risk for depression (MDD). Preventive measures targeting this often remotely living population might reduce depression burden. The study aimed to evaluate the effectiveness of personalized telephone coaching in reducing depressive symptom severity and preventing MDD in farmers compared to enhanced treatment as usual (TAU + ). Methods In a two-armed, pragmatic randomized controlled trial (N = 314) with post-treatment at 6 months, farming entrepreneurs, collaborating family members and pensioners with elevated depressive symptoms (PHQ-9 >= 5) were randomized to personalized telephone coaching or TAU + . The coaching was provided by psychologists and consists on average of 13 (+/- 7) sessions a 48 min (+/- 15) over 6 months. The primary outcome was depressive symptom severity (QIDS-SR16). Results Coaching participants showed a significantly greater reduction in depressive symptom severity compared to TAU + (d = 0.39). Whereas reliable symptom deterioration was significantly lower in the intervention group compared to TAU + , no significant group differences were found for reliable improvement and in depression onset. Further significant effects in favor of the intervention group were found for stress (d = 0.34), anxiety (d = 0.30), somatic symptoms (d = 0.39), burnout risk (d = 0.24-0.40) and quality of life (d = 0.28). Discussion Limiting, we did not apply an upper cutoff score for depressive symptom severity or controlled for previous MDD episodes, leaving open whether the coaching was recurrence/relapse prevention or early treatment. Nevertheless, personalized telephone coaching can effectively improve mental health in farmers. It could play an important role in intervening at an early stage of mental health problems and reducing disease burden related to MDD.
CRIS-Team WoS Importer:2022-07-01